Mapping the root systems of individual trees in a natural community using genotyping‐by‐sequencing. Issue 3 (26th December 2022) - Osborne, Owen G.; Dobreva, Mariya P.; Papadopulos, Alexander S. T.; de Moura, Magna S. B.; Brunello, Alexandre T.; de Queiroz, Luciano P.; Pennington, R. Toby; Lloyd, Jon; Savolainen, Vincent
Summary: The architecture of root systems is an important driver of plant fitness, competition and ecosystem processes. However, the methodological difficulty of mapping roots hampers the study of these processes. Existing approaches to match individual plants to belowground samples are low throughput and species specific. Here, we developed a scalable sequencing‐based method to map the root systems of individual trees across multiple species. We successfully applied it to a tropical dry forest community in the Brazilian Caatinga containing 14 species. We sequenced all 42 individual shrubs and trees in a 14 × 14 m plot using double‐digest restriction site‐associated sequencing (ddRADseq). We identified species‐specific markers and individual‐specific haplotypes from the data. We matched these markers to the ddRADseq data from 100 mixed root samples from across the centre (10 × 10 m) of the plot at four different depths using a newly developed R package. We identified individual root samples for all species and all but one individual. There was a strong significant correlation between belowground and aboveground size measurements, and we also detected significant species‐level root‐depth preference for two species. The method is more scalable and less labour intensive than the current techniques and is broadly applicable to ecology, forestry and agricultural biology. Abstract : See also the Commentary on this article by Jones, 238 : 924–925 .